If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4z + -1) + -5(z + 1) = 3(z + 1) Reorder the terms: 3(-1 + 4z) + -5(z + 1) = 3(z + 1) (-1 * 3 + 4z * 3) + -5(z + 1) = 3(z + 1) (-3 + 12z) + -5(z + 1) = 3(z + 1) Reorder the terms: -3 + 12z + -5(1 + z) = 3(z + 1) -3 + 12z + (1 * -5 + z * -5) = 3(z + 1) -3 + 12z + (-5 + -5z) = 3(z + 1) Reorder the terms: -3 + -5 + 12z + -5z = 3(z + 1) Combine like terms: -3 + -5 = -8 -8 + 12z + -5z = 3(z + 1) Combine like terms: 12z + -5z = 7z -8 + 7z = 3(z + 1) Reorder the terms: -8 + 7z = 3(1 + z) -8 + 7z = (1 * 3 + z * 3) -8 + 7z = (3 + 3z) Solving -8 + 7z = 3 + 3z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-3z' to each side of the equation. -8 + 7z + -3z = 3 + 3z + -3z Combine like terms: 7z + -3z = 4z -8 + 4z = 3 + 3z + -3z Combine like terms: 3z + -3z = 0 -8 + 4z = 3 + 0 -8 + 4z = 3 Add '8' to each side of the equation. -8 + 8 + 4z = 3 + 8 Combine like terms: -8 + 8 = 0 0 + 4z = 3 + 8 4z = 3 + 8 Combine like terms: 3 + 8 = 11 4z = 11 Divide each side by '4'. z = 2.75 Simplifying z = 2.75
| 3y-12=7 | | .05=.6m | | 3x^2+4+1= | | -.75k=.67 | | -13x^3+20x-7=0 | | 18=-.5t | | -4d+2(4+9)=-14 | | 0.083n=12 | | 9m-13=-22+8m | | 36y=108 | | x^3-x^2-1120=0 | | x=-3y^2-12y | | 3(x-4)-2(x+2)-13=-20 | | (3x-12)-2x+-2-13=-20 | | 3x-12-2x+4-13=20 | | 24x^3-21x^2= | | (3x-12)-2x+(-2)-13=-20 | | -4=8-s | | 2-(y+2)=y | | 46x^3+43x^2+5x= | | 2-(y+2)=ey | | 2x(x+3)=12 | | 3x-12+16=2x+10 | | X+5x=3 | | 5x+17-4x=9+4x-7 | | x+7m=78m^2 | | 346*65=x | | 4x+7x-3x=34+6 | | -10x+(-5)-x=28 | | -10x+5-x=28 | | 34*15=x | | -3y-3=1+2y |